2013
DOI: 10.1016/j.virol.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomics of Aedes albopictus salivary gland, midgut and C6/36 cell induced by dengue virus infection

Abstract: The interaction between dengue virus (DENV) and vector mosquitoes are still poorly understood at present. In this study, 2-D DIGE combined with MS was used to analyze the differential proteomes of Aedes albopictus salivary gland, midgut and C6/36 cells induced by DENV-2. Our results indicated that the virus infection regulated several functional classes of proteins. Among them, 26 were successfully analyzed by real-time RT-PCR. The mRNA levels of 15 were the highest in salivary gland, 2 in midgut and none in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Consistent with enzymes that are linked to protection, energy production, and protein metabolism, proteins that participate in signaling and transport (14-3-3 and WD40) [31,32] were also abundant in the NE. Interestingly, in the A. aegypti larvae midguts infected with CHIKV, WD-repeat proteins were highly expressed [5], while expression of 14-3-3 proteins was low in the midgut of mosquitoes infected with DENV-2 [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with enzymes that are linked to protection, energy production, and protein metabolism, proteins that participate in signaling and transport (14-3-3 and WD40) [31,32] were also abundant in the NE. Interestingly, in the A. aegypti larvae midguts infected with CHIKV, WD-repeat proteins were highly expressed [5], while expression of 14-3-3 proteins was low in the midgut of mosquitoes infected with DENV-2 [30].…”
Section: Resultsmentioning
confidence: 99%
“…Four other proteins related to protein metabolism were abundant in the NE and BF: glutamate dehydrogenase, aspartate aminotransferase, PDI and calreticulin [20,[27][28][29]. Calreticulin and PDI are highly expressed during DENV-2 and CHIKV infection of the midgut, respectively, may be involved in the replication, translation, and/or viral encapsidation [5,30]. Three proteins involved in cell signaling -14-3-3 protein (NE72), 14-3-3 protein epsilon (YWHAE; NE71), and WD40-repeat (NE38)were identified, as well as proteins involved in transport: RabGEF (NE48), proteins that form voltage dependent ion channels (VDAC; NE41) and V-ATPase (BF18).…”
Section: Resultsmentioning
confidence: 99%
“…This effect was more significant in the depolymerization of microtubules that in actin microfilaments. It has been reported that viral infections alter the global host proteomic in response to these, including cytoskeletal proteins [87][88][89]. However, although a role for the involvement of these proteins in viral infection is hypothesized, a route through which this occurs has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. albopictus [25,27,28], analysis of the actual saliva reveals reduced amounts of adenosine deaminase, aegyptin, and serpin [24]. Infection of Ae.…”
Section: Effects Of Environmental Factors and Pathogens In The Expresmentioning
confidence: 99%